Sustainable human settlements within the global urban agenda : formulating and implementing SDG 11 - Simon, David (Agenda Publishing, 2024)
The UN's urban sustainability goal (#11) is fundamental to the global sustainable development agenda. David Simon explains the anatomy and dynamics of SDG 11, and critically assess how it is being used and understood in different local, regional and national contexts.
Keywords: Sustainable Development Goals (Project); Sustainable urban development -- Cross-cultural studies.; Urbanisme durable -- Études transculturelles.; Sustainable urban development; Cross-cultural studies